Use of Rhizobacteria and Mycorrhizae Consortium in the Open Field as a Strategy for Improving Crop Nutrition, Productivity and Soil Fertility - Raklami, Anas; Bechtaoui, Noura; Tahiri, Abdel-ilah; Anli, Mohamed; Meddich, Abdelilah; Oufdou, Khalid (Frontiers in Microbiology, 2019)
Plant growth promoting rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) are known for their beneficial effects. In recent years, more attention has been paid to their use as biofertilizers to reduce the use of chemical fertilizers causing significant damage to the environment. To have high plant yields, biofertilizers may not be able to sustain plant demands and could be used in combination with chemical fertilizers. However, the application of biofertilizers in the field such as rhizobacteria and AMF are understudied and powerfully needed. In this context, this study aims to evaluate the effect of inoculation with rhizobacteria and AMF and their potential to stimulate two of the most economically important crops in Mediterranean semi-arid areas (Vicia faba L. and Triticum durum L.). The effect of inoculation was studied in field experiment with six treatments: i) the control without inoculation (C), ii) PGPR alone (PG), iii) rhizobia alone (R), iv) the mixture of PGPR and rhizobia (PR), v) AMF alone (M) and vi) the mixture of PGPR, rhizobia and AMF (PRM). The inoculation with the consortium of PGPR-rhizobia-AMF induced the greatest effect. This inoculation improved the growth parameters (dry weight of shoots and roots) of faba bean and wheat. An improvement of 130%, 200% and 78% was observed in V. faba shoot and root dry weight, and the number of leaves respectively. Similarly, shoot and root dry weight and number of leaves of T. durum were enhanced by 293%, 258% and 87% respectively. The inoculation improved the productivity of studied plants presented by the number and weight of bean pods (270 ×104 ha-1 and 30737.5 kg.ha-1) and wheat spikes (440 ×104 ha-1 and 10560 kg.ha-1). In addition, the mineral analyses showed that the inoculation with PGPR-rhizobia-mycorrhizae improved N, P, Ca, K, and Na shoots contents, as well as the contents of sugar and proteins. Finally, we revealed the positive impact of the tested biofertilizers and the interest of adoption of innovative practices improving crops productivity and soil fertility.